Half-Blind to the Risk of Predation - Beauchamp, Guy (Frontiers in Ecology and Evolution, 2017)
Blinking serves several functions in animals, but it comes at the cost of intermittent blindness. Blinking can occur spontaneously, but it is commonly associated with head movements. As feeding animals often need to move the head down repeatedly to gather resources, intermittent blindness might represent a hitherto unappreciated cost of feeding. In addition, this cost might also be more prevalent in larger groups as feeding effort typically increases with group size. In chickens (Gallus gallus domesticus), blinks associated with head movements occurred at a high frequently during feeding bouts. While blinks tended to be short, the amount of time spent blinking was close to 50% when feeding and increased with group size. By contrast, time spent blinking was much lower when birds simply monitored their surroundings between feeding bouts. Intermittent blinking at this scale when feeding is likely to decrease the ability to detect predation threats in a timely fashion and to monitor neighbors effectively.